(untitled) (Ocean and Coastal Research, 2022)
The present study sought to provide information on the variations in abundance of migratory bird populations in relation to seasonality, reinforcing the significance of Ilha Comprida on the migration route, as a stopping point for this fauna group’s resting and feeding. The Ilha Comprida beach was travelled by car during low tide, at an average speed of 40 km/h, following a 70-km by 200-meter predetermined transection. During the study period between January and December 2016, a total of 9134 individuals from 26 species of migratory birds were registered. This environment receives migrant species from both the Northern and Southern Hemispheres, increasing species richness primarily in September and October. The lowest wealth of birds and smallest number of individuals was recorded on the beach during June, July, and August. This study shows that many birds leave Ilha Comprida in late May and return in September.